Poking cells for efficient vector-free intracellular delivery - Wang, Ying; Yang, Yang; Yan, Li; Kwok, So Ying; Li, Wei; Wang, Zhigang; Zhu, Xiaoyue; Zhu, Guangyu; Zhang, Wenjun; Chen, Xianfeng; Shi, Peng (Nature communications, 2014)
Techniques for introducing foreign molecules and materials into living cells are of great value in cell biology research. A major barrier for intracellular delivery is to cross the cell membrane. Here we demonstrate a novel platform utilizing diamond nanoneedle arrays to facilitate efficient vector-free cytosolic delivery. Using our technique, cellular membrane is deformed by an array of nanoneedles with a force on the order of a few nanonewtons. We show that this technique is applicable to deliver a broad range of molecules and materials into different types of cells, including primary neurons in adherent culture. Especially, for delivering plasmid DNAs into neurons, our technique produces at least eightfold improvement (~45% versus ~1–5%) in transfection efficiency with a dramatically shorter experimental protocol, when compared with the commonly used lipofection approach. It is anticipated that our technique will greatly benefit basic research in cell biology and also a wide variety of clinical applications. The incorporation of foreign objects into cells can be used in various avenues of biological research, although crossing the cell membrane can be challenging. Here, the authors use a diamond nanoneedle array for enhanced delivery of various particles into cells, including neurons.